IMPLEMENTASI ETIKA EKOLOGIS DALAM KONSERVASI LINGKUNGAN: : TAWARAN SOLUSI DARI AL-QUR’AN - Nur Afiyah Febriani (Sekolah Tinggi Agama Islam Sadra, 2014)
This paper tries to compare between anthroposentrical paradigm and a theory of conservation called by ecocentrism, the theory try to combine the universal teachings of holy book and science on safeguarding of stable ecosystem of the world. By using thematic method (this method usually applied in investigating several contemporary problems belong to people in the term of contextualization of Holy Book’s message which in this case is al-Qur’an), and supporting by the scientific approach from East and West, this paper expounds the description of al-Qur’an on the concept of ecological ethics which encompassed in a theory which I call with ecohumanist-theocentric. This theory necessarily demands a harmonious inter-connection and interaction between human being and himself (ḥabl ma‘a nafsih), human beingand other human beings (ḥabl ma‘a ikhwānih), human being and nature (ḥabl ma‘a bī’atih), human being andGod (ḥabl ma‘a khāliqih). This implementation of universal teachings of al-Qur’an for world’s society is considered as an applicative and comprehensive solution which is offered by al-Qur’an in the way to answer theproblems of environmental harm.